EFEKTIVITAS MEDIA DAKWAH ISLAM DALAM MENANGGULANGI BERITA HOAKS - Budi Santoso; Rochman R; Totok Yuswiyanto; Lallo Hamid (Al-Idaroh: Media Pemikiran Manajemen Dakwah, 2025)
: The spread of hoaxes has become a significant challenge in the digital era. False information can lead to division, trigger slander, and disrupt social harmony. In the context of Islam, hoaxes contradict the teachings that prioritize truth and honesty. Islamic da’wah media has great potential to serve as an effective tool in combating hoaxes. This study aims to explore the effectiveness of Islamic da’wah media in countering hoaxes from the perspective of Islamic teachings, supported by evidence from the Qur'an, Hadith, Ijma, and Qiyas. The consensus of Islamic scholars (Ijma) agrees that spreading falsehoods is forbidden, and through Qiyas, the dissemination of hoaxes in digital media is analogous to slander, which is also prohibited. This study employs a qualitative approach with a literature review and data analysis from various sources. The results show that Islamic da’wah media is effective in combating hoaxes through three main strategies: promoting the teaching of tabayyun, enhancing digital literacy among the community, and providing accurate information based on Islamic values. Additionally, collaboration between da’wah media, religious leaders, and government institutions is a key factor in its success. In conclusion, Islamic da’wah media can act as a stronghold against hoaxes if utilized strategically and wisely. Rooted in Islamic teachings, da’wah media contributes to preserving unity among Muslims and educating society on the importance of honesty and responsibility in communication.